Semantic and Syntactic Dimensional Analysis of Rural Wooden Mosque Architecture in Borçka - Birgül Çakıroğlu; Reyhan Akat; Evren Osman Çakıroğlu; Taner Taşdemir (Buildings)
Religion is one of the most important factors in architectural shaping. The concepts or sub-concepts that make up religion have a different language that each designer wants to explain. This language is presented semantically and syntactically through the architect and the user interprets this fiction mostly with its syntactic dimension. The findings of this study provide valuable insights into modern mosque design by establishing a connection between belief systems and architectural expressions. Moreover, the study contributes to heritage preservation efforts by proposing a framework that links historical values to contemporary practices. In this study, it is aimed to analyze the effects of the belief concepts in the Islamic religion by analyzing the semantic and syntactic dimensions in rural wooden mosque architecture. Starting from the assumption that abstract values have a language in shaping, the principle of semiotics was utilized to reach concrete results. How the concepts and principles are determined in the semantic and syntactic dimensions of semiotics are explained. In the examination of the semantic dimension, 5 concepts from the concepts of belief in the Islamic religion, namely wahdaniyet, survival, knowledge, powerand hereafter, were discussed. The syntactic dimension was analyzed under basic design principles. The semantic and syntactic dimensions of the sample wooden mosques were analyzed, interpretedand analyzed through architectural drawings, interiorand exterior visuals. These analyses provide practical strategies for translating abstract religious principles into tangible design elements, enhancing their applicability in both educational and professional contexts. As a result, the concepts that emerged in the analyzed examples and the indicators of the sub-concepts belonging to these concepts were presented. It is suggested that the determined analysis model can contribute to design education in design departments and provide convenience to designers and researchers. The model also serves as a tool for creating mosque designs that respect cultural identity while addressing contemporary needs. This research is important in terms of being a reference for the concrete expression of the concepts that we cannot see in architectural formations but we can feel that they exist.